UPAYA MENINGKATKAN KEMAMPUAN NILAI TEMPAT PADA PEMBELAJARAN MATEMATIKA MENGGUNAKAN MEDIA MAZE BAGI ANAK TUNAGRAHITA RINGAN KELAS DIV/C - Yulia - Efda (Universitas Negeri Padang, 2013)
The studies aim of this is to increase the understanding of the concept of place value on a child's mild mental retardation (Kh, Ph and Sm) in class DIV / C in District 20 Nan Balimo SDLB SMF through the maze of media use on the material value of the place. Type of research is a classroom action research (classroom action research) that takes the form of collaboration. The results showed that during the first cycle of six sessions held in the learning process that starts from listening to the teacher's explanation about; put the number corresponding value, write and complete the exercise. Based on the average of 10 questions obtained Ph before the given action obtain a value of 20, and after being given the action I got 60. Kht before given their scores of 20 and after being given the action I got 50. And before the given action Sm obtain the value of 30, and after got a score of 70. While on the second cycle Ph scored 80, Kh cycle II gets a score of 70, and Sm the second cycle got 90 marks . From the results presentation and analysis of the data it can be concluded that the use of media maze can enhance the value of spot placement mild mental retardation in children DIV classes / C. Thus it can be suggested to the schools, teachers, and researchers can use the following to the media maze to improve their understanding of the value of a place for children mild mental retardation.